E-prints Intersect the Digital Library: Inside the Los Alamos arXiv. - Richard E. Luce (Issues in Science and Technology Librarianship)
The e-print arXiv at the Los Alamos National Laboratory acts as a repository for electronic versions of papers in physics and mathematics, providing a rapid and convenient way for scientists to rapidly share their results with colleagues. Recently the arXiv was transferred to the Research Library, as part of its Library Without Walls. This article traces the development of the arXiv and examines some of the implications for libraries. Opportunities and challenges exist to integrate new forms of scholarly communication with newly developed digital library services offered by leading-edge libraries.